IMPLEMENTASI HUKUM ISLAM DALAM PRAKTIK EKONOMI ISLAM DI INDONESIA - Farida, Ulfa Jamilatul (Ekonomi Syariah STAI Sangatta Kutai Timur, 2019)
Islamic economic developments in the country, covering an academic study in universities or in practice operasioanl as happened in the Islamic economic institutions such as Islamic Banking, Takaful, Islamic Capital Market, and so on. The development is expected to further broaden to include aspects and a very broad scope, such as economic policy, local economics, macroeconomic (fiscal policy, public finance, strategy to overcome poverty and unemployment, inflation, monetary policy), and other economic issues, such as wage and labor and others. In the development of economic institutions in order to compete and in accordance with the needs of modern business society, necessary to create innovative products to remain in compliance with Shariah principles in its operations. The development also has implications for many Indonesian people who move in an Islamic economy, it is very possible legal disputes in the field of Islamic economics. Therefore, it takes the application of Islamic law in the practice of Islamic economics in Indonesia.Walaupun seem a bit slow when compared to the rise of Islamic economic institutions in Indonesia, but the presence of Islamic Economics Law Compilation (KHES) in Indonesia in late 2008 and should be appreciated by good. KHES least is a new breakthrough in the economic aspects of Islamic legal thought in Indonesia. Application of Islamic law in the practice of Islam in other Indonesian economy is the implementation of DSN MUI fatwas that ensures products and operations of Islamic economic institutions in Indonesia are in accordance with Islamic principles.